Real-time training and coaching methods based on ubiquitous technologies - an illustration of a mobile coaching framework - Novatchkov, H.; Bichler, S.; Tampier, M.; Kornfeind, P. (International Journal of Computer Science in Sport, 2011)
Ubiquitous methods and technologies are well-established in modern society. Pervasive computing techniques are also widely used in the field of sport. This article gives an overview of some typical implementations and fields of application regarding the use of pervasive computing in sports competition and training. Moreover, it presents our current focus on the field of "Mobile Coaching" as one specific ubiquitous approach. This includes our research goals and objectives as well as the methodology, practical scenarios and implemented results of the framework.